Investigation of electrical conductivity and electromagnetic interference shielding performance of Au@CNT/sodium alginate/polydimethylsiloxane flexible composite. (March 2020) - Lei, Xing; Zhang, Xinrui; Song, Anran; Gong, Shen; Wang, Yang; Luo, Liuxiong; Li, Teng; Zhu, Zhenghong; Li, Zhou
Abstract: Flexible electromagnetic shielding composite material has good deformation ability and stable electromagnetic shielding performance. In this paper, Au@CNT/sodium alginate/polydimethylsiloxane flexible composites are prepared by infiltrating PDMS polymer into Au@CNT/sodium alginate sponge skeleton. Nano-scale Au particles coated on CNT surface can effectively improve the electrical conductivity and electromagnetic shielding performance of the composite. The experimental results show that the log function values of conductivity and electromagnetic shielding performance obey a quasi linear relationship. After 10% elastic tensile strain, the conductivity of all samples are remain unchanged, which indicate a stable electromagnetic shielding performance under strain. Combined with the multi-scale model analysis, the mechanism of electrical stability and the effect of Au sizes and cladding rate are discussed. Calculation results show that the electromagnetic shielding performance of the flexible composite sample could reach more than 60 dB. These flexible shielding composites with stable performance under strain may have good application potential, such as for wearable smart electronics.